QR code: a pedagogical proposal in the Physical Education teacher training - Luz, Fernanda Soares (2020)
Digital technologies are increasingly present in daily life and have boosted the emergence of new teaching practices. At that, this study aimed to present the pedagogical possibilities of Quick Response Codes through an experiment made in a semi-presence minicourse in which a competition named GymCode was used as a pedagogical strategy. For this purpose, a qualitative research was carried out with 15 students enrolled in the latter half of the Physical Education Teaching Course. The data collected through the questionnaire answered by the participants were analyzed according to the theoretical framework. It was found that the QR code technology can be used by teachers as a pedagogical resource to mediate student knowledge. It is expected that the study will contribute and encourage reflections on the use of digital technologies in the teaching and learning process.